Six Sigma in preconstruction: case study on improving of reinforcement steel processing - Pap, Reka Zsofia; Szűcs, Edit (International Journal of Engineering and Management Sciences, 2024)
Lean process improvements are crucial for enhancing production efficiency. In my research, I examine the application of the DMAIC methodology to develop the MEP facility within the framework of lean Six Sigma. Highlighting the challenges of precast concrete production, my study details how lean management aids in efficient process design and measurement. Introducing lean Six Sigma methodology involves standardizing processes and ensuring their effective development, contributing to the facility’s efficiency